The Caliph Abd ar-Rahman al-Nasir in Arabic and Turkish Literature: A comparative study between ʿAbdūl-ḥaqq Ḥāmid and Georgy Zeidan - Abdulsattar Elhajhamed (Şarkiyat Mecmuası)
The Umayyad Caliph Abd ar-Rahman al-Nasir is one of the important figures who left an impact on history. During his rule, which was nearly fifty years, Andalusia witnessed development and prosperity in the scientific, administrative, political, military, and urban fields. He attracted the attention of writers of books, stories, novels, and plays in various languages. Among those who dealt with this character were the Turkish writer ʿAbdūl-ḥaqq Ḥāmid in the play Tezer or Malik Abd ar-Raḥmān III and Georgy Zeidan in the novel ‘Abd ar-Rahmân al-Nasir. This study deals with the character of ‘Abd ar-Rahman al-Nasir in these two literary works that bear his name. In the introduction, Abd ar-Rahman al-Nasir and the most important literary works that embodied him are introduced, and then a proposal is made for the two works under study. The comparison section notes the points of difference and similarity of the character of Abd ar-Rahman in the two works. The reasons for the difference in the presentation of this character, which is the purpose of summoning or writing about it, were also indicated. The research concludes that the two writers participated in presenting this historical character in the framework of a fictional story, but they differed in the formulation and use of this character. Although ʿAbdūl-ḥaqq Ḥāmid portrayed it as an ideal figure, Georgy Zeidan portrayed it negatively.